Pretreatment conditions of palm oil mill effluent (POME) for thermophilic biohydrogen production by mixed culture. (9th November 2017) - Mahmod, Safa Senan; Jahim, Jamaliah Md; Abdul, Peer Mohamed
Abstract: The availability of fermentable sugars in POME is one of the critical factors that determine the fermentative biohydrogen production yield. This study was carried out to determine the pretreatment conditions viz., temperature, hydrolysis time and acid concentration that can yield the highest monomeric sugars, to be utilized for production of biohydrogen from POME by mixed culture dark fermentation. Two different acids were used, nitric acid and phosphoric acid in the pretreatment of POME. Batch fermentation was performed to determine the potential of pretreated POME as a substrate for the production of biohydrogen under the tested pretreatment conditions. Higher hydrogen yield was successfully achieved using pretreated POME as compared to raw POME by mixed culture. Maximum hydrogen production was 0.181 (mmol/L/h), which corresponded to the yield of 1.24 mol H2 /mol glucose achieved at 0.8% (w/v) phosphoric acid with initial total reducing sugar concentration of 18.47 g/L. Hence, the results implied that POME pretreated with 0.8% (w/v) phosphoric acid is a potential substrate for efficient biohydrogen fermentation yield that is 97% higher than untreated POME. While POME pretreated with 1% (w/v) of nitric acid showed 65% improvement in biohydrogen yield as compared to untreated POME. Therefore, the results implied that both pretreatment methods of POME showed significant increase in the biohydrogen production. Highlights: Dilute acid pretreatment is applied on palm oil mill effluent POME to increase its solubility. POME hydrolysate was used for thermophilic biohydrogen production by mixed culture. Pre-treated POME showed higher biohydrogen yield than raw POME.